1999
DOI: 10.1007/s002800050965
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer exffect of 9-nitrocamptothecin liposome aerosol on human cancer xenografts in nude mice

Abstract: 9-NC liposome aerosol was strikingly effective in the treatment of three human cancer xenografts growing subcutaneously over the thorax in nude mice at doses much smaller than those traditionally used in mice administered by other routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 28 publications
1
68
0
Order By: Relevance
“…8,9 Also, we previously reported that aerosol delivery of a liposomal formulation of 9NC, a topoisomerase I inhibitor, can inhibit the growth of subcutaneous tumors as well as lung metastases. 10,11 In this report, we demonstrate that sequential delivery of p53 and 9NC by aerosol can arrest the growth of established B16-F10 melanoma pulmonary metastases in experimental mice.In order to study the combined effect of 9NC and p53 in vitro, B16-F10 cells grown in tissue culture plates were transfected with PEI-p53 or PEI-Neobam complexes (1 …”
mentioning
confidence: 63%
See 1 more Smart Citation
“…8,9 Also, we previously reported that aerosol delivery of a liposomal formulation of 9NC, a topoisomerase I inhibitor, can inhibit the growth of subcutaneous tumors as well as lung metastases. 10,11 In this report, we demonstrate that sequential delivery of p53 and 9NC by aerosol can arrest the growth of established B16-F10 melanoma pulmonary metastases in experimental mice.In order to study the combined effect of 9NC and p53 in vitro, B16-F10 cells grown in tissue culture plates were transfected with PEI-p53 or PEI-Neobam complexes (1 …”
mentioning
confidence: 63%
“…Both the p53 gene and the camptothecins have been reported to inhibit subcutaneous tumor growth, as well as lung metastases, alone and in combi- nation with other agents. 8,10,11,14,15 Our data demonstrate for the first time that sequential aerosol delivery of p53 and 9NC can inhibit the growth of established B16-F10 lung metastases.…”
mentioning
confidence: 64%
“…Preliminary studies were performed in mice using the subcutaneous human lung tumor xenograft and human osteosarcoma pulmonary metastasis models. The first experiment showed a significant reduction in tumor volume in animals treated with aerosolized 9NC-DLPC, even compared to groups of animals receiving the same dose orally or intramuscularly (Knight et al, 1999). In the metastases model, the aerosolized formulation of the camptothecin derivative showed the capacity to reduce the number of animals with disease and the number and size of lung nodules in the fraction of animals showing pulmonary metastases (Koshkina et al, 2000).…”
Section: Nanocarrier Formulations Administered As Liquid Aerosolsmentioning
confidence: 99%
“…This highlights the need to (8), is believed to act by stabilizing the topoisomerase I-induced DNA single strand break, so as to preventing religation (9). As a strong inhibitor of the DNA-replicating enzyme topoisomerase I (10), camptothecin has many novel activities, such as antitumor, antiproliferative effects and induces cell apoptosis in a large amount of cancer cell lines, especially in human xenografts of colon, lung, breast, ovarian, and melanoma cancers (11)(12)(13)(14). Additionally, camptothecin also showed promising potential of antimetastasis in a broad spectrum of cancers, such as melanoma, ovarian cancer, colon, pancreatic cancer (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%